THE CORRELATION BETWEEN KNOWLEDGE AND BEHAVIOR OF VULVA HYGIENE WITH PATHOLOGICAL LEUKORRHEA INCIDENCE - Putri, Widiya; Mita, Mita; Rahmawati, Nadia (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Vulva hygiene is important to prevent pathological vaginal discharge. Adolescent girls are susceptible to such discharge due to insufficient awareness of proper hygiene practices. A preliminary study identified instances of improper wiping techniques and failure to adequately dry the vulva before donning underwear among students. Moreover, some students reported experiencing genital itching. The purpose of this study was to determine the correlation between knowledge and behavior of vulva hygiene with pathological vaginal discharge This study employed a correlational cross-sectional design. The population consisted of 52 female students at Al-Hasani Islamic Boarding School, selected through total sampling. Data were collected using validated and reliable questionnaires. Statistical analysis utilized Kendall's Tau correlation test. This research has passed an ethical review with letter number 1450/UN22.9/PG/2024 which considers research ethics in the form of informed consent, anonymity, privacy, confidentiality, justice, and beneficience. The results are 65.4% of respondents had good knowledge of vulva hygiene, 53.8% exhibited good vulva hygiene behavior, and 50% experienced pathological leucorrhea. Correlation analysis revealed no significant correlation between knowledge (ρ value = 0.087) or behavior (ρ value = 0.582) of vulva hygiene and pathological leucorrhea incidence. Further research is needed regarding factors associated with the occurrence of pathological vaginal discharge.